Pengukuran Stating Point Dimensi Strategi Inovasi Studi Pada Pusat Pengembangan Sumber Daya Manusia Aparatur Esdm - Hendris Agung Prasojo; Dian Anggarini (Pusat Pengembangan Sumber Daya Manusia Aparatur, 2021)
ABSTRACTThe Center for Human Resources development for the ESDM Apparatus is a training institution that provides soft skills and hard skills training, so that PPSDMA can act as an example for other institutions within the Ministry of Energy and Mineral Resources. PPSDMA can adapt to ongoing changes, because it demands continuous innovation so that the organization can be sustainable. The purpose of this research is that PPSDMA can find out the current position of innovation, by measuring the organizational innovation stating point. This study classifies the dimensions and levels of innovation at PPSDMA, Ministry of Energy and Mineral Resources. Each dimension was measured using a questionnaire to employees at PPSDMA. The results of the measurement of the eight innovation strategies are processed quantitatively and statistically and the minimum score is 2.54 and the maximum score is 3. 09. The average score obtained is 2.83 is a sufficient score, which is in the middle position so that PPSDMA is at the stating point as a hopeful innovator. PPSDMA has a spirit of innovation, even though the organization is inclined towards gradual improvement rather than making innovations that change internal business process patterns. Likewise, the organizational approach is still ad hoc and unstructured. PPSDMA should take a systematic view of the core strategic, customer-focused, and focus on the organizational factors needed for the innovation strategy and immediately look for